Whipple’s disease – a clinical case - Silva, Marisa (2002)
The authors present the case of a 61 year-oldpatient, admitted with a clinical picture characterizedby digestive haemorrhage, and weight loss.After investigation the diagnosis of Whipple diseasewas made.Antibiotic therapy with trimethoprim-sulfamethoxazolewas efficacious and was followed by arapid improvement of clinical and laboratory parameters